Use of Aloe Vera Gel Coating as Preservative on Tomato - Roy, Ambuza; Karmakar, Anindita (International Journal of Bio-resource and Stress Management, 2019)
Tomato is highly demanded in the market because of its high nutritional value. But Tomato has a very short shelf life due to its perishable nature. Short shelf life coupled with improper processing facilities results in heavy socio-economic loss. Aloe veragel mainly composed of polysaccharides has been recently explored as an effective edible coating to increase the shelf life of fruits and vegetables because of its antifungal and antimicrobial activity. Hence, the present study was conducted to evaluate the effect of aloe vera coating on shelf life of tomato. Tomatoes were washed, surface water was removed and then coated with aloe vera gel. After coating fruit surface was air dried and kept at refrigerated condition (5±1 oC, 90-95% RH). The various physicochemical properties like moisture content, physiological loss in weight, total soluble solid content, ascorbic acid content, colour and firmness were measured at a regular interval for both uncoated and coated tomatoes for a storage period of 21 days. Aloe vera gel coated tomatoes were found to maintain their moisture, colour and firmness better than the uncoated ones. They also showed lesser reduction in physiological weight loss, ascorbic acid content and total soluble solid content. The uncoated tomatoes showed rapid deterioration and almost 90% of tomatoes were decayed after 21 days of storage whereas aloe vera coated tomatoes showed no deterioration within this period and only 10% of the coated tomatoes were decayed after 28 days of storage.